KEABSAHAN JUAL BELI OLEH ANAK DIBAWAH UMUR MENURUT MADZHAB HANAFI DAN SYAFI’I - Aziz, Abd; Bahruddin (Irtifaq, 2019)
This article discusses the validity of buying and selling byunderage children according to Hanafi and Syafi'i. It is known that thepractice of it in Islam must meet the conditions that have beendetermined, one of which is adult in thinking, with his own will, notselfish, and adult in view (baligh). However, in practice there are manytraders who sell food or snacks to children who have not entered the ageof baligh (underage). Buying and selling by children who are underage inIslamic law has been a difference of clerics' opinions, namely the Hanaficonsiders that little children have not received a legal burden, whereasthe Syafi'i considers it illegitimate because underage children areineligible. Keywords: Validity, Buying and Selling, Underage Children